The missing link: The challenge of achieving economic as well as environmental sustainability in remote ASEAN rainforest communities - Yeo, Alvin; Richards, Cameron (2013)
The dilemma of being relatively self-sufficient but connected to the world is one which faces even remote and indigenous ASEAN rainforest communities. Such communities may well provide an important key to a future globally networked society balancing or reconciling the often conflicting agendas of economic and environmental sustainability. This paper explores the common challenges and opportunities faced in distinct yet related rainforest communities in remote parts of Mindanao in the Philippines and Sarawak in Malaysia as they grapple with the central dilemma of linking up to the world yet also retaining a reasonable degree of resilience and self-sufficiency in the face of change.It will do so in terms of an integrated model of different kinds of knowledge and capacity needing to be better linked and reconciled when new challenges of adaptation and resource optimization are laced in time as well as in space.